2016
DOI: 10.1111/pirs.12225
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of city growth in Colombia

Abstract: I develop a systematic approach to examine the drivers of population growth in Colombian cities between 1993 and 2010. Fertility plays an important role. Much of the higher growth of some Colombian cities can also be associated with higher wages. In turn, this wage advantage of some cities can be, in part, traced back to city education and industry shocks. I also find that roads and connectivity matter but obtained mixed evidence about the role of urban amenities and no evidence regarding measures of urban cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 43 publications
5
35
0
3
Order By: Relevance
“…The estimations confirm that the ease to access markets mattered for local employment growth during the boom years. In this sense, the results are also in line with previous results in the literature that have shown that accessibility, and with it transportation infrastructure, matters for local growth (e.g., da Mata et al., ; Duranton, ; Duranton & Turner, ). For the recession period, however, the instrumental variable estimations indicate no significant effect of market potential on the resilience of municipalities.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The estimations confirm that the ease to access markets mattered for local employment growth during the boom years. In this sense, the results are also in line with previous results in the literature that have shown that accessibility, and with it transportation infrastructure, matters for local growth (e.g., da Mata et al., ; Duranton, ; Duranton & Turner, ). For the recession period, however, the instrumental variable estimations indicate no significant effect of market potential on the resilience of municipalities.…”
Section: Resultssupporting
confidence: 91%
“…Local employment growth depends on a range of factors which have been analyzed in a now large literature on urban growth (see, e.g., Cheshire & Magrini, 2006, 2009da Mata, Deichmann, Henderson, Lall, & Wang, 2007;Duranton, 2016;Duranton & Turner, 2012;Glaeser, Kallal, Scheinkman, & Shleifer, 1992;Glaeser, Scheinkman, and Shleifer, 1995;Glaeser & Saiz, 2004;Henderson et al, 1995;Simon, 1998). Studies related to rural growth (Ganning, Baylis, & Lee, 2013;Lavesson, 2017;Partridge et al, 2007Partridge et al, , 2008aPartridge et al, , 2008b and papers that have considered both types of locations (see, e.g., Ahrend & Schumann, 2014;Beeson, DeJong, & Troesken, 2001;Combes, 2000;Desmet & Fafchamps, 2005;Saito & Wu, 2016, Veneri & Ruiz, 2016 have also studied the determinants of local growth.…”
Section: Determinants Of Local Employment Growthmentioning
confidence: 99%
“…In the Supporting Information, a table reports results where the share of education is instrumented by the number of local higher education institutions and the number of the positions for the local branch of the national technical university (SENA). I use a similar instruments when regressing population growth on city education in Duranton (). Although the instruments are strong, the coefficients on city education is in most cases insignificant but typically around 0.50.…”
Section: Results About Human Capital Externalities Market Access Inmentioning
confidence: 99%
“…A worry might be then be that population is driven by these amenities. This conjecture is examined in Duranton () where I examine the determinants of city growth in Colombia between 1993 and 2010. I only find a modest role for amenities.…”
Section: Results About Human Capital Externalities Market Access Inmentioning
confidence: 99%
“…The paper by Duranton () explains city growth in Colombia. He includes a more comprehensive set of determinants than previous research, providing an elaborate review of a wide variety of factors that are essential to understand urban growth, and simultaneously sketches how these factors can best be empirically explored from the modelling point of view.…”
Section: Contents Of the Special Issuementioning
confidence: 99%